2002
DOI: 10.1046/j.1524-4725.2002.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Temporal Alopecia Following Rhytidectomy: The Prophylactic Use of Minoxidil. a Study of 60 Patients

Abstract: On comparing our findings to results of larger rhytidectomy series in which minoxidil was not used prophylactically, and our experience before using minoxidil, we conclude that minoxidil plays a role in effectively preventing the temporal hair loss that occurs following primary cervicofacial rhytidectomies. We also found that minoxidil did not negatively impact on the risk of hematoma formation, skin necrosis, edema, or ecchymosis. Side effects of minoxidil did not present a problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…Based on all this evidence, the authors concluded that localized telogen effluvium could have been the cause of temporary hair loss after rhytidectomy. Moreover, a study reported that preoperative and postoperative prophylactic use of minoxidil reduces the percentage of hair loss that occurs after rhytidectomy 5 , and this finding also supported our conclusion.…”
supporting
confidence: 90%
“…Based on all this evidence, the authors concluded that localized telogen effluvium could have been the cause of temporary hair loss after rhytidectomy. Moreover, a study reported that preoperative and postoperative prophylactic use of minoxidil reduces the percentage of hair loss that occurs after rhytidectomy 5 , and this finding also supported our conclusion.…”
supporting
confidence: 90%
“…Owsley 7 and Owsley and Fiala 8 described one of the earliest versions, and others, including the senior author, have described minor variations of the technique. 9, 10 Sasaki and cohen also describe good results with a far more complex GoreTex cable suture method. Elevation of the mid-face continues to remain one of the major challenges of face-lift surgery.…”
mentioning
confidence: 96%
“…No permanent alopecia was developed during the follow-up and only 1.7% of temporary alopecia was presented in patients using minoxidil prophylactically compared to other studies where the same surgical technique was used, that reported 2-3% of permanent alopecia and 5-8% of temporary alopecia. 9 No other side effects or complications were found with the use of topical minoxidil and may be a prophylactical option in patients undergoing rhytidectomy.…”
Section: Acute Telogen Effluviummentioning
confidence: 94%
“…No specific treatment has been described to prevent or accelerate regrowth. A previously mentioned study used topical minoxidil for temporal alopecia after rhytidectomy and suggested it may play a role in hair loss in patients at risk of alopecia 9 . .…”
Section: Thread Lift Proceduresmentioning
confidence: 99%